HISTOLOGICAL STRUCTURE OF THE IMMUNE SYSTEM ORGANS (THYMUS, LYMPH NODES, SPLEEN) AND AGE-RELATED CHANGES (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article provides a detailed overview of the deep histological structure, cellular and stromal components, functional zones, as well as age-related morphological and functional changes of the main primary and secondary lymphoid organs of the immune system: the thymus, lymph nodes, and spleen. It covers the differentiation of thymocytes in the cortex and medulla of the thymus, types of epithelial cells, Hassall’s corpuscles, the blood-thymus barrier, and thymic nurse cells; the follicles, germinal centers, paracortex, high endothelial venules, follicular dendritic cells, and medullary sinuses of the lymph nodes; and the white pulp, periarteriolar lymphoid sheath, marginal zone, macrophage populations, and red pulp of the spleen. Age-related changes, particularly thymic involution associated with adipogenesis, fibrosis, degeneration of epithelial cells, and decreased expression of the FOXN1 gene; fibrosis, lipomatosis, and stromal transdifferentiation in lymph nodes; and de-compartmentalization of the white pulp, disruption of the marginal zone, and increased fibroblasts in the spleen are comprehensively described as key processes of immunosenescence.